Cloud Based Video on Demand Model with Performance Enhancement - Lavanya, R.; Ramachandran, V. (Malaysian Journal of Computer Science, 2011)
Today Internet has become an integral part of most of our life. The attempt to display media files through Internet was started from the mid-20th century. Several research works have been reported to provide Video on Demand model in distributed environments like RMI, Component based, SOA and Grid computing. Inspite of these developments, it is been understood that very little progress has been made for several decades, primarily due to the high cost and limited capabilities of computer hardware and standards. Thus it is necessary to develop a model that is reliable, scalable and cost-effective. The proposed research work aims to implement the Video on Demand Service in Cloud Environment in a more secure, scalable and cost effective manner. The performance measures like upload time and download time are analyzed with different video files of varying sizes that are divided into block blobs of 32KB, 64KB and 1MB and are reported.